PERANAN DAN TANGGUNG JAWAB PEMERINTAH DALAM PELAYANAN KESEHATAN PASCA DISAHKANNYA OMNIBUS LAW TENTANG KESEHATAN - Benyamin Dicson Tungga (Nusantara Hasana Journal, 2023)
The purpose of this research is to examine the role and responsibility of the government in health services after the ratification of the Health Omnibus Act. This study also aims to convey the idea of ​​a comprehensive health law as a national legal policy aimed at improving the health of the Indonesian people. This article uses normative legal research methods using legal approaches, contextual approaches, and analytical approaches. This study shows that the idea of ​​a comprehensive health law as a national legal policy to improve public health status in Indonesia is both a challenge and an opportunity. Considering that the health sector makes an important contribution to the sustainability of the development goals put forward by the United Nations, one of the goals of sustainable development is to lead a healthy and prosperous life. Therefore, regulations based on Pancasila values ​​must be revised and harmonized both nationally and internationally to ensure the achievement of the task of promoting fair, just and affordable companies with legal certainty.